Systematic review of the Dasymutilla monticola species-group (Hymenoptera: Mutillidae): using phylogenetics to address species-group placement and sex associations - Williams, Kevin A.; Manley, Donald G.; Deyrup, Mark; Von Dohlen, Carol; Pitts, James P. (Zootaxa, 2012)
Using the internal transcribed spacer regions (ITS) 1 and 2, the phylogeny of the Dasymutilla monticola species-group is reconstructed. The purpose of this analysis is to determine the monophyly of the D. monticola species-group and to determine the species-group placement of numerous unplaced Dasymutilla species. Taxonomic changes are made based on these results. New synonymy is proposed for Mutilla birkmani Melander 1903, ♀ (=Dasymutilla corcyra Mickel 1928, ♀, syn. nov.; =Dasymutilla arcana Mickel 1928, ♂, syn. nov.), Mutilla macilenta Blake 1871, ♂ (=Dasymutilla chattahoochei Bradley 1916, ♀, syn. nov.), Dasymutilla saetigera Mickel 1928, ♀ (=Dasymutilla polia Mickel 1928, ♂, syn. nov.). The currently associated male of D. chattahoochei belongs to D. arenerronea (♀), stat. resurr., which was previously recognized as a synonym of D. chattahoochei. The currently recognized male of D. archboldi belongs to D. vesta; the true male of D. archboldi is newly described. Dasymutilla vesta, D. radkei, and D. archboldi are transferred into the D. monticola species-group. A male identified as D. fasciventris (♂), which has gray apical tergal setae like many males of the D. monticola species-group, was recognized as a member of the D. quadriguttata species-group; the true D. fasciventris was not studied. Dasymutilla chalcocephala (♀) and D. spilota (♀), which bear a superficial resemblance to the D. monticola species-group, are determined to not belong to any currently recognized species-group. Inferences are made about the homology of tubercles on the female’s posterior margin of the head, the necessity for phylogenetic research on species-group placement, and the necessity for both morphological and molecular data.